Design and Implementation LETS (Low Power Cluster Server) for Sustaining UMKM during Pandemic - Sidharta, Hanugra Aulia; Sidharta; Filipi, Felix; Jaskandi, Rafli Attala; Nugroho, Febrian (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2021)
Covid pandemic is spreading since end 2019 arround globe, this resulting several countries suffer economic crisis. Due people movement restriction and international border is closed, impact halting on export and import. Indonesia with 267,7 million people manage to overcome global crisis during 1998 and 2008 with encourage small and local industry. According data from BPS, SME support 60% GDP with Rp 7,7 Billion and provide 85 million employment. To sustain SME during customer shifting behavior, we propose small cluster server called as LETS. LETS is modular, and composed with several Raspberry Pi 4, also consume few energies compared with traditional server. Although Raspberry Pi 4 is small size with few limitations, with lightweight application (ansible, k3s, and nginx) it can provide web server service. LETS provide handling traffic up to 742 simultaneus requests, which sufficient of SME requirement.